9 Box Model Talent Management: Potential Review Assessment on Bank Employees - Ketut Ayu Pratithi Widnyanadita; Dewi Syarifah (Psikostudia : Jurnal Psikologi, 2023)
Potential review individual assessment research is carried out as a form of talent management activity to obtain a comprehensive picture of the subject's potential and what competencies that still need to be developed. The tool used to determine potential competencies and their current and long-term contribution to the organization is the 9-box model. The subjects in this study were 1 person who was an employee at PT Bank X. The subject had just served as a Corporate Culture Supervisor. This study used two data collection methods, the test method (psychological test kits and work samples) and non-test (interview). Data were analyzed using descriptive analysis and qualitative analysis. The results of the study show that in the 9-box model analysis, the subject is included in the "future star" category, which is in the range of moderate performers and high potential in the talent pool of PT Bank X. This proves that the subject is a potential cadre to occupy the position of Corporate Culture Supervisor at PT Bank X. Penelitian asesmen individu potential review dilakukan sebagai bentuk kegiatan talent management untuk memperoleh gambaran secara komprehensif mengenai potensi yang dimiliki oleh subjek serta kompetensi apa yang masih perlu untuk dikembangkan. Tools yang digunakan untuk menentukan potensi kompetensi dan kontribusi mereka saat ini dan jangka panjang bagi organisasi adalah 9-box model. Subjek pada penelitian ini sebanyak 1 orang yang merupakan karyawan pada PT Bank X. Subjek baru saja menjabat sebagai Penyelia Corporate Culture. Penelitian ini menggunakan dua metode pengumpulan data, yaitu metode tes (alat tes psikologi dan work sample) dan non tes (wawancara). Data dianalisis dengan menggunakan analisis deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa dalam analisis 9-box model, subjek termasuk dalam kategori “future star”, yang berada pada rentang moderate performer dan high potential dalam talent pool PT Bank X. Hal tersebut membuktikan bahwa subjek termasuk kader potensial untuk menduduki jabatan Penyelia Corporate Culture pada PT Bank X.